SLE presenting as multiple hemorrhagic complications. (September 2015) - Abdulla, M C; Alungal, J; Hashim, S; Ali, M M; Musambil, M
A 24 year old female with hereditary spastic paraplegia presented with intermittent headache for one year. She also had lower abdominal pain and vomiting for two months. She was pale, had icterus and mild splenomegaly. On diagnostic evaluation she was found to have hemolytic anemia, thrombocytopenia and bilateral adrenal, subdural, soft tissue (scalp and orbit) hemorrhages due to systemic lupus erythematosus (SLE). However, antiphospholipid syndrome (APS) antibodies were negative. Bilateral adrenal hemorrhage without associated APS is a rare phenomenon in SLE. We describe a case of SLE presenting with sequence of rare hemorrhagic complications in concert.